An Environment for detection of Bugs through SVM (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2015)
Mining technique finds hidden patterns from the data stored in the repositories and turn it into useful information and knowledge. Most open source software development projects include an open bug repository in which users of the software can gain full access. Training data size for bug priority classification using SVM.In this paper, calculate the precision and recall of different features categories for each class. The bug report having status value NEW, UNCONFIRMED, ASSIGNED bugs are not included in our training .because the priority level of these classifications may not be authentic. A trigger’s task is to manage the bug repository so that it contains only real bugs and important bugs are addressed quickly. We also use the precision and recall that can be used to measure the accuracy of the classifier. For a bug priority classification we need high precision and recall especially for higher priorities.